Bile acids and their receptors in metabolic disorders. (April 2021) - Fiorucci, Stefano; Distrutti, Eleonora; Carino, Adriana; Zampella, Angela; Biagioli, Michele
Abstract: Bile acids are a large family of atypical steroids which exert their functions by binding to a family of ubiquitous cell membrane and nuclear receptors. There are two main bile acid activated receptors, FXR and GPBAR1, that are exclusively activated by bile acids, while other receptors CAR, LXRs, PXR, RORγT, S1PR2and VDR are activated by bile acids in addition to other more selective endogenous ligands. In the intestine, activation of FXR and GPBAR1 promotes the release of FGF15/19 and GLP1 which integrate their signaling with direct effects exerted by theother receptors in target tissues. This network is tuned in a time ordered manner by circadian rhythm and is critical for the regulation of metabolic process including autophagy, fast-to-feed transition, lipid and glucose metabolism, energy balance and immune responses. In the last decade FXR ligands have entered clinical trials but development of systemic FXR agonists has been proven challenging because their side effects including increased levels of cholesterol and Low Density Lipoproteins cholesterol (LDL-c) and reduced High-Density Lipoprotein cholesterol (HDL-c). In addition, pruritus has emerged as a common, dose related, side effect of FXR ligands. Intestinal-restricted FXR and GPBAR1 agonists and dual FXR/GPBAR1 agonists have been developed. Here we review the last decade in bile acids physiology and pharmacology.